Metallized slurry and preparation method and application thereof
By adding polydimethylsiloxane-modified fumed silica to the metallization slurry, the problems of uneven metal slurry dispersion and metallization layer thickness differences during the screen printing process are solved, achieving more uniform printing. and higher metallization layer quality.
Patent Information
- Application Number
- CN202411560912.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-21
AI Technical Summary
During screen printing, the metal paste is unevenly dispersed, resulting in thicker edges and thinner middles of the metallized layer, and the shape is not preserved after printing, making it easy to peel.
Use a metallization slurry containing 17.5%-18.1% solvent, 0.9%-1.5% ethyl cellulose and 80.4%-81% metal mixed powder, in which 0.2%-1% polydimethylsilane is added to the metal mixed powder Oxane modified fumed silica to improve the thixotropy and rheology of the slurry.
By adding modified fumed silicon oxide, the quality of the metallization layer is improved, the problems of uneven dispersion and shape instability are solved, the thickness difference is reduced, and the tensile strength is improved.
Smart Images

Figure CN119339991A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal slurries, and in particular relates to a metallization slurry and a preparation method and application thereof. Background Art
[0002] The vacuum interrupter is the core switch device in the medium voltage circuit, and its vacuum degree is the key parameter of the device. The vacuum degree of the device is achieved by sealing and welding the ceramic tube and the metal cover in a vacuum furnace, and the welding layer is the metallization layer, that is, the metal slurry is printed on the ceramic end surface by screen printing and sintered.
[0003] The quality of the metallization layer directly affects the sealing level between the ceramic and the metal cover. In order to avoid false printing and leveling in the process, the viscosity of the metal slurry is usually low. The metal slurry is unevenly dispersed during the screen printing process. After printing, the metal slurry needs to be dried in an oven immediately to maintain its shape. This method requires that the ceramic parts be stored flat after screen printing and the time interval between entering the oven is short, which puts forward stricter operating requirements for production. In addition, the metallization layer printed by this process shows an overall trend difference of thicker edges and thinner middle. Summary of the invention
[0004] The purpose of the present invention is to provide a metallization slurry and a preparation method and application thereof, which solves the problem of uneven dispersion of metal slurry during screen printing and the overall trend difference of the metallization layer being thicker at the edge and thinner in the middle.
[0005] The present invention is achieved through the following technical solutions:
[0006] The invention discloses a metallization slurry, which comprises, by mass percentage, 17.5%-18.1% of a solvent, 0.9%-1.5% of ethyl cellulose and 80.4%-81% of a metal mixed powder;
[0007] In terms of mass percentage, the metal mixed powder includes 60%-70% molybdenum powder, 10%-15% manganese powder, 10%-15% aluminum oxide powder, 5%-10% silicon oxide powder, 1%-5% magnesium oxide powder, and 0.2%-1% polydimethylsiloxane-modified fumed silica.
[0008] Furthermore, the solvent is pineol.
[0009] Further, the preparation process of the polydimethylsiloxane-modified fumed silica is as follows:
[0010] Under the condition of 150-250° C., dimethylsiloxane and fumed silica are mixed and ground for 5-10 hours to prepare polydimethylsiloxane fumed silica.
[0011] The present invention also discloses a method for preparing the metallization slurry, comprising the following steps:
[0012] 1) Preparing metal mixed powder;
[0013] Mix the solvent terpineol and ethyl cellulose, heat and stir to fully dissolve the ethyl cellulose;
[0014] 2) Mixing the dissolved ethyl cellulose with the metal mixed powder, ball milling and sieving to obtain a metallized slurry.
[0015] 5. In step 1), the parameters of heating and stirring are: heating at 110-140°C and stirring at a speed of 1-2 r / min.
[0016] Further, in step 2), ball milling specifically comprises: grinding in a ball mill for 18-24 hours.
[0017] The invention also discloses the use of the metallization slurry in preparing a vacuum arc extinguishing chamber. The metallization slurry forms a metallization layer, and the metallization layer serves as a transition layer connecting metal and ceramic.
[0018] Further, the qualified metallization slurry is screen-printed on the end surface of the alumina ceramic tube, and sintered at 1400-1500° C. to obtain a metallized ceramic pipe fitting;
[0019] Wherein, during sintering, sintering is carried out in a sintering atmosphere of hydrogen and nitrogen atmosphere;
[0020] After electroplating the metallized ceramic pipe fittings, the metallized ceramic pipe fittings are placed in a vacuum furnace, silver-copper solder is placed between the metal cover plate and the metallized layer, and then vacuumed and heated for welding, so that the metal cover plate and the ceramic parts are connected to each other.
[0021] Compared with the prior art, the present invention has the following beneficial technical effects:
[0022] The invention discloses a metallization slurry, wherein polydimethylsiloxane-modified fumed silica is used in a metal mixed powder to replace part of the silicon oxide in the glass component of the traditional metallization slurry formula, and part of the polydimethylsiloxane-modified fumed silica is used to replace the crystalline silica, so as to form a new formula system, improve the thixotropy of the metal slurry, and thus improve the quality of the metallization layer. The modified fumed silica can be dissolved smoothly in pine alcohol, and the polydimethylsilane group can form a three-dimensional winding network in pine alcohol to form a thixotropic structure; at the same time, the surface of part of the unmodified fumed silica forms hydrogen bonds with the hydroxyl group in pine alcohol to produce thixotropy. The polydimethylsiloxane-modified fumed silica can increase the thixotropic performance of the metallization slurry, solve the problems of uneven dispersion of the metal slurry during screen printing, the inability of the metallization layer to keep its shape after printing, the uneven edges and corners of the metallization layer, and the peeling; after adding the modified fumed silica, the tensile strength of the metallization layer is slightly increased, and the product performance is not affected. In summary, the present invention replaces the glass powder component in the original metal slurry formula with crystalline powder that forms glass, and uses part of modified gas-phase silicon oxide instead of crystalline silicon oxide, so that the metallization slurry exhibits stronger thixotropic properties, thereby reducing the storage and drying requirements for silk-screen products, while reducing the thickness difference of the metallization layer, and omitting the process of preparing glass powder from crystalline powder.
[0023] Since the polydimethylsilane group can form a three-dimensional winding network in pine alcohol, the viscosity of the metallization paste tends to decrease when the shear force increases; when the shear force disappears, the viscosity of the metallization paste increases. This feature can well meet the requirements of screen printing, that is, when the paste is printed, the viscosity of the paste immediately decreases due to the shear force and spreads on the surface of the printed porcelain, but when the shear force is removed, the viscosity of the paste increases immediately, ensuring the printed shape and reducing the dispersion of the paste, resulting in uneven paste.
[0024] Furthermore, by replacing the glass powder in the original formula with polydimethylsiloxane-modified fumed silica, the process of preparing the crystal powder into a glass body and then quenching and grinding it with water is omitted.
[0025] The present invention also discloses an application of a metallization slurry in the preparation of a vacuum interrupter. The production of the metallized ceramic parts of the vacuum interrupter is to screen-print a metal paste on a sintered ceramic, so the metal paste will shrink to a certain extent during the sintering process. The shrinkage rate of sintering is certain, but the actual shrinkage value depends on the end face width of the screen-printed ceramic part. For ceramic parts with a larger end face width, the shrinkage rate remains unchanged, but the actual shrinkage value becomes larger. Because the ceramic parts have been sintered and will not shrink again, the metallization layer of the ceramic parts with a wider end face is prone to peeling during sintering.
[0026] Due to the addition of inorganic polydimethylsilane-modified gas silicon, some organic additives in the metal slurry can be replaced (the content of ethyl cellulose, pine alcohol, hydrogenated castor oil, etc. is reduced), reducing the shrinkage of the ceramic metallization layer during the sintering process, thereby reducing the peeling phenomenon of the wide surface metallization layer caused by excessive shrinkage values. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The rheological characteristic curve of the metallization slurry prepared by the present invention;
[0028] Figure 2 This is a picture of the anti-sagging properties of the metallization paste prepared in the present invention after printing and placed vertically for 0 hours; wherein, Figure a is a picture of the anti-sagging properties of the metallization paste prepared in the comparative example; Figure b is a picture of the anti-sagging properties of the metallization paste prepared in Example 4;
[0029] Figure 3 This is a picture of the anti-sagging properties of the metallization paste prepared by the present invention after printing and placing vertically for 1 hour; wherein, Figure a is a picture of the anti-sagging properties of the metallization paste prepared in the comparative example; Figure b is a picture of the anti-sagging properties of the metallization paste prepared in Example 4. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clear, the following is further described in detail with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, not all embodiments.
[0031] The components described and shown in the drawings and embodiments of the present invention may be arranged and designed in various configurations. Therefore, the detailed description of the embodiments of the present invention provided in the following drawings is not intended to limit the scope of the claimed invention, but merely represents a selected embodiment of the present invention. Based on the drawings and embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0032] It should be noted that the terms "comprises", "includes" or any other variations are intended to cover non-exclusive inclusion, so that a process, element, method, article or equipment that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to the process, element, method, article or equipment.
[0033] The invention discloses a metallization slurry, which comprises, by mass percentage, 17.5%-18.1% of a solvent, 0.9%-1.5% of ethyl cellulose and 80.4%-81% of a metal mixed powder;
[0034] In terms of mass percentage, the metal mixed powder includes 60%-70% molybdenum powder, 10%-15% manganese powder, 10%-15% aluminum oxide powder, 5%-10% silicon oxide powder, 1%-5% magnesium oxide powder, and 0.2%-1% polydimethylsiloxane-modified fumed silica.
[0035] The preparation process of the polydimethylsiloxane modified fumed silica is as follows:
[0036] Under the condition of 150-250° C., dimethylsiloxane and fumed silica are mixed and ground for 5-10 hours to prepare polydimethylsiloxane fumed silica.
[0037] The corresponding performance verification of metallization paste is divided into the following aspects:
[0038] a) The rheological properties of the slurry were tested using a viscometer.
[0039] b) The slurry was screen-printed onto a 95 alumina ceramic tile and then placed vertically for 1 hour to compare and observe the anti-sagging properties of the metallization slurry.
[0040] c) sintering the silk-screened ceramic piece at 1400-1500° C. in a sintering furnace in a hydrogen and nitrogen atmosphere to obtain a metallized ceramic piece;
[0041] After the metallized ceramic parts are electroplated, they are connected using silver-copper solder, and the sealing strength of the metallized layer is tested using the three-point bending method.
[0042] The metallization pastes prepared in the following examples were all verified using the above verification method, which will not be described in detail.
[0043] The features and performances of the present invention are further described in detail below in conjunction with the embodiments.
[0044] Example 1
[0045] This embodiment discloses a method for preparing a metallization slurry, comprising the following steps:
[0046] 1) Add 17.5 g of terpineol and 1 g of ethyl cellulose into a stirring tank, heat and stir to fully dissolve the ethyl cellulose.
[0047] 2) The dissolved ethyl cellulose was transferred into a ball mill, and 81.5 g of metal mixed powder was added. The mixture was ground in the ball mill for 18 hours and passed through a 300-mesh sieve to obtain a metallized slurry, which was recorded as Sample 1.
[0048] Wherein, in terms of mass percentage, the metal mixed powder includes 60% molybdenum powder, 15% manganese powder, 15% aluminum oxide powder, 4.6% silicon oxide powder, 5% magnesium oxide powder, and 0.4% polydimethylsiloxane-modified fumed silica.
[0049] Example 2
[0050] This embodiment discloses a method for preparing a metallization slurry, comprising the following steps:
[0051] 1) Add 18 g of terpineol and 1.5 g of ethyl cellulose into a stirring tank, heat and stir to fully dissolve the ethyl cellulose.
[0052] 2) The dissolved ethyl cellulose was transferred into a ball mill, and 80.5 g of metal mixed powder was added. The mixture was ground in the ball mill for 24 hours and passed through a 300-mesh sieve to obtain a metallized slurry, which was recorded as Sample 2.
[0053] Wherein, in terms of mass percentage, the metal mixed powder includes 65% molybdenum powder, 13% manganese powder, 10% aluminum oxide powder, 9.4% silicon oxide powder, 2% magnesium oxide powder, and 0.5% polydimethylsiloxane-modified fumed silica.
[0054] Example 3
[0055] This embodiment discloses a method for preparing a metallization slurry, comprising the following steps:
[0056] 1) Add 18.1 g of terpineol and 1.5 g of ethyl cellulose into a stirring tank, heat and stir to fully dissolve the ethyl cellulose.
[0057] 2) The dissolved ethyl cellulose was transferred into a ball mill, and 80.4 g of metal mixed powder was added. The mixture was ground in the ball mill for 24 hours and passed through a 300-mesh sieve to obtain a metallized slurry, which was recorded as Sample 3.
[0058] Wherein, in terms of mass percentage, the metal mixed powder includes 70% molybdenum powder, 10% manganese powder, 11.2% aluminum oxide powder, 5% silicon oxide powder, 3% magnesium oxide powder, and 0.8% polydimethylsiloxane-modified fumed silica.
[0059] Example 4
[0060] This embodiment discloses a method for preparing a metallization slurry, comprising the following steps:
[0061] 1) Add 18 g of terpineol and 0.9 g of ethyl cellulose into a stirring tank, heat and stir to fully dissolve the ethyl cellulose.
[0062] 2) The dissolved ethyl cellulose was transferred into a ball mill, and 81.1 g of metal mixed powder was added. The mixture was ground in the ball mill for 24 hours and passed through a 300-mesh sieve to obtain a metallized slurry, which was recorded as Sample 4.
[0063] Wherein, in terms of mass percentage, the metal mixed powder includes 63% molybdenum powder, 12% manganese powder, 13% aluminum oxide powder, 10% silicon oxide powder, 1% magnesium oxide powder, and 1% polydimethylsiloxane-modified fumed silica.
[0064] When used, the qualified metallization slurry is screen-printed on the end face of the alumina ceramic tube, and sintered at 1400-1500°C to obtain the metallized ceramic pipe fittings;
[0065] Wherein, during sintering, sintering is carried out in a sintering atmosphere of hydrogen and nitrogen atmosphere;
[0066] After electroplating, the metallized ceramic tube is placed in a vacuum furnace, silver-copper solder is placed between the metal cover plate and the metallized layer, and then vacuumed for 10 -5 Pa, the temperature rises to 850℃, and the metal cover can be connected to the porcelain part. Since this sealing is carried out in a vacuum furnace, the vacuum degree inside the ceramic tube is the same as that of the vacuum furnace, which can achieve the vacuum degree required by the vacuum interrupter.
[0067] The glass component in the original metal slurry formula is glass powder, while the improved formula uses crystal powder that forms glass, which can reduce the process of dissolving the powder into glass, then quenching with water and then grinding.
[0068] Comparative Example 1
[0069] The difference from Example 4 is that the preparation of the metal mixed powder is different, and the final prepared product is recorded as Sample 5.
[0070] In terms of mass percentage, the metal mixed powder includes 63% molybdenum powder, 12% manganese powder, 13% aluminum oxide powder, 11% silicon oxide powder, and 1% magnesium oxide powder.
[0071] Comparative Example 2
[0072] The difference from Example 4 is that the preparation of the metal mixed powder is different, and the final prepared product is recorded as Sample 6.
[0073] In terms of mass percentage, the metal mixed powder includes 63% molybdenum powder, 12% manganese powder, 13% aluminum oxide powder, 11% silicon oxide powder, 1% magnesium oxide powder, and 1% fumed silicon dioxide.
[0074] Comparative Example 3
[0075] Different from Example 4, the preparation of the metal mixed powder is different, and the final prepared product is recorded as Sample 7.
[0076] In terms of mass percentage, the metal mixed powder includes 63% molybdenum powder, 12% manganese powder, 13% aluminum oxide powder, 11% silicon oxide powder, 1% magnesium oxide powder, and 1.5% polydimethylsiloxane-modified fumed silica.
[0077] The performance of the above four embodiments and comparative examples is verified, specifically from four aspects: rheological properties, anti-sagging properties, metallization layer thickness difference and metallization layer strength.
[0078] 1. Rheological properties
[0079] Get as Figure 1 The results shown are from Figure 1 It can be seen that when 0% of the fumed silica metallization slurry is added, the shear speed is from 10-100RPM and the viscosity is basically maintained at 20,000cps.
[0080] At a shear rate of 10RPM, the viscosity of the metal slurry increased from 20,000cps to about 70,000cps as the amount of fumed silica added increased, but at a high shear rate of 100RPM, the viscosity increased from 20,000cps to 26,000cps, and the viscosity remained basically unchanged.
[0081] The metallization paste prepared in the embodiment of the present invention has high viscosity when there is no shear force or low shear force; when the shear force is high, the viscosity of the paste decreases. This characteristic can well meet the requirements of screen printing, that is, when the paste is printed, the viscosity of the paste immediately decreases due to the effect of the shear force and spreads on the surface of the printed porcelain, but after the shear force is removed, the viscosity of the paste increases immediately, ensuring the printed shape and reducing the dispersion of the paste, resulting in uneven paste.
[0082] 2. Anti-sagging properties
[0083] Figure 2 Figure a in the figure is a sample without adding fumed silica, i.e., sample 5 prepared in the comparative example; Figure 2 Figure b shows a sample with 1% fumed silica added. Figure 2 It can be seen that after the metallization paste without adding silicon dioxide is printed (vertically placed for 0 hours), the edge forms an arc shape due to the surface tension of the liquid.
[0084] After standing vertically for 1 hour, Figure 3 As shown in Figure a, the slurry without fumed silica flows to the bottom, forming a circular liquid-solid boundary. Figure 2 Figure b and Figure 3As shown in Figure b, the boundaries of the metal slurry are clear after being placed vertically for 0 hours and 1 hour, and there is no sign of slurry flow, which well maintains the boundary accuracy and uniformity of screen printing.
[0085] 3. Thickness deviation of metallization layer after screen printing
[0086] The two ends and the middle part of the metallized layer were measured by X-ray fluorescence thickness gauge. The ceramic parts with the end face width of 5.5mm were used for comparative test.
[0087]
[0088]
[0089] From the table above, we can see that after adding 1% modified gas silicon, the thickness difference between the middle and two edges of the metallization layer can be significantly reduced during the screen printing process. This is because, during the screen printing process, when the screen is lifted after printing, the metallization slurry adheres to the screen. After adding gas silicon, the slurry viscosity increases sharply after the screen stops printing, and the screen can be disconnected from the slurry in a very short time, maintaining the increase in edge thickness caused by the accumulation of slurry at the edge.
[0090] After adding 1.5% modified gas silica, the viscosity of the slurry increased during the screen printing process, the metallized layer printed on the porcelain piece became intermittent, and the metallized layer showed obvious screen printing patterns, and the paste could not flow level.
[0091] After adding unmodified fumed silica in Comparative Example 2, it could not be dissolved in the mixed solvent of terpineol, and the fumed silica floated on the surface of the solvent. When the prepared paste was screen-printed, no obvious thixotropy improvement effect was shown.
[0092] 4. Metallization layer strength
[0093] The metallization pastes prepared in the above four embodiments and the samples prepared in the comparative example were subjected to strength tests, and the results are shown in Table 1.
[0094] Table 1
[0095]
[0096] In summary, vapor phase silicon oxide can greatly change the performance of metallization paste, solving the problems of uneven dispersion and poor conformal properties of metal paste during screen printing. After adding vapor phase silicon oxide, the tensile strength of the metallization layer is slightly increased, which does not affect the product performance.
[0097] After the silicon oxide in the formula is replaced by modified fumed silica, the replaced part of the fumed silica plays two roles. The first is to improve the rheological properties of the slurry before the metallization slurry is sintered: the slurry produces thixotropy and has dispersion properties for metal powders. The second role is to produce a sintering solvent in the formula, which is the same as the original silica.
[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A metallization paste, characterized in that: In terms of mass percentage, it comprises 17.5%-18.1% solvent, 0.9%-1.5% ethyl cellulose and 80.4%-81% metal mixed powder; In terms of mass percentage, the metal mixed powder includes 60%-70% molybdenum powder, 10%-15% manganese powder, 10%-15% aluminum oxide powder, 5%-10% silicon oxide powder, 1%-5% magnesium oxide powder, and 0.2%-1% polydimethylsiloxane-modified fumed silica.
2. The metallization paste according to claim 1, characterized in that: The solvent used is pinene alcohol.
3. The metallization paste according to claim 1, characterized in that: The preparation process of the polydimethylsiloxane modified fumed silica is as follows: Under the condition of 150-250° C., dimethylsiloxane and fumed silica are mixed and ground for 5-10 hours to prepare polydimethylsiloxane fumed silica.
4. The method for preparing the metallization paste according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) Preparing metal mixed powder; Mix the solvent terpineol and ethyl cellulose, heat and stir to fully dissolve the ethyl cellulose; 2) Mixing the dissolved ethyl cellulose with the metal mixed powder, ball milling and sieving to obtain a metallized slurry.
5. The method for preparing a metallization paste according to claim 4, characterized in that: In step 1), the parameters of heating and stirring are: heating at 110-140° C. and stirring at a speed of 1-2 r / min.
6. The method for preparing a metallization paste according to claim 4, characterized in that: In step 2), ball milling specifically comprises: grinding in a ball mill jar for 18-24 hours.
7. Use of the metallization slurry according to any one of claims 1 to 3 in preparing a vacuum interrupter, characterized in that: The metallization paste forms a metallization layer, and the metallization layer serves as a transition layer connecting metal and ceramic.
8. The use of the metallization slurry according to claim 7 in preparing a vacuum interrupter, characterized in that: The qualified metallization slurry is screen-printed on the end surface of the alumina ceramic tube, and sintered at 1400-1500°C to obtain a metallized ceramic pipe fitting; Wherein, during sintering, sintering is carried out in a sintering atmosphere of hydrogen and nitrogen atmosphere; After electroplating the metallized ceramic pipe fittings, the metallized ceramic pipe fittings are placed in a vacuum furnace, silver-copper solder is placed between the metal cover plate and the metallized layer, and then vacuumed and heated for welding, so that the metal cover plate and the ceramic parts are connected to each other.